Clinical Trial Perspective: Cost-effectiveness of Transcatheter Mitral Valve Repair Versus Medical Therapy in Patients with Heart Failure and Secondary Mitral Regurgitation. Results From the COAPT Trial - Suzanne J Baron (US Cardiology Review)
Treatment of secondary (or functional) mitral regurgitation had traditionally been limited to optimal medical therapy because studies have failed to show a survival benefit with mitral valve surgery for this condition. However, recently the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation (COAPT) trial demonstrated a significant decrease in heart failure hospitalizations and mortality in patients with severe secondary mitral regurgitation treated with percutaneous edge-to-edge mitral valve repair (TMVr) using the MitraClip device compared with medical therapy. Based o the results of the COAPT trial, the Food and Drug Administration granted approval for MitraClip treatment of patients with severe secondary mitral regurgitation in March 2019. In an attempt to understand the economic impact of treating this patient population with TMVr using the MitraClip device, a formal cost-effectiveness analysis was performed alongside the COAPT trial. This review summarizes the methods and results of the economic substudy of the COAPT trial and discusses the value of the MitraClip device from the perspective of the US healthcare system in the treatment of patients with symptomatic heart failure and secondary mitral regurgitation.